Constitutional and Legal Issues in Ghana’s Public Administration: Governance and Public Policy Challenges - Fobih, Nick (Advances in Social Sciences Research Journal, 2021)
The purpose of this study is to examine some of the major constitutional and legal issues that are imperative in Ghana’s public administration. Despite Ghana’s success in promoting democratic governance over the past decades since the 1992 transition, numerous constitutional and legal issues affect effective policy design and implementation that require urgent governmental reforms. The study discussed the constitutional and democratic theories as the basis of the work. The methodology used is based on the qualitative approach with combined sources from primary and secondary data. The findings in the study show that certain aspects of Ghana’s constitutional provisions and legal framework do adversely affect its policy design and implementation in diverse ways. The significance of the study is that the outlined challenges and recommendations will inform the government and key policy makers on the need to make effective policies in order to enhance the country’s political and socio-economic development. The study’s implication for theory is that it will inform its readers about the different theoretical perspectives on the issues discussed. The study also provides key insights into important issues in Ghana’s constitutional provisions, and the legal and policy environment, which can serve as useful tools or instruments for policy makers in the three organs of government and the bureaucracy. This study further contributes towards academic discussions on the viability of the constitutions drawn by authoritarian regimes prior to the third-wave democratic transitions in Africa, and the difficulties some of these constitutional provisions pose to making effective policies and governance, thus emphasizing the need for constitutional reviews.